The Hands-on Guide to Practical Prescribing. - Jones, Oliver (Hands-on Guides., 2008)
The hands-on guide to practical prescribing is a concise, easy-to-use guide to the practical aspects of pharmacology for junior doctors who are making the transition from studying pharmacology to prescribing drugs for the first time. This new addition to 'The hands-on guide' series brings together the core pharmacological knowledge required by house officers, structured in a way to address the very hands-on, practical aspects of prescribing. This book is not designed to replace the factual drug information in the BNF, but to complement and build upon it, so that The hands-on guide to practical.